Respuesta :

Simplifying
7y + -4 = 3y + 6

Reorder the terms:
-4 + 7y = 3y + 6

Reorder the terms:
-4 + 7y = 6 + 3y

Solving
-4 + 7y = 6 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-4 + 7y + -3y = 6 + 3y + -3y

Combine like terms: 7y + -3y = 4y
-4 + 4y = 6 + 3y + -3y

Combine like terms: 3y + -3y = 0
-4 + 4y = 6 + 0
-4 + 4y = 6

Add '4' to each side of the equation.
-4 + 4 + 4y = 6 + 4

Combine like terms: -4 + 4 = 0
0 + 4y = 6 + 4
4y = 6 + 4

Combine like terms: 6 + 4 = 10
4y = 10

Divide each side by '4'.
y = 2.5

Simplifying
y = 2.5